Road Performance Analysis in Maliana District, Bobonaro Regency, Timor Leste - godinho, domingos; Teki Tjendani, Hanie; Wulandari, Esti (International Journal Labs, 2025)
Transportation is an important part that cannot be separated from human life, as it plays a crucial role in various aspects, including socio-cultural, economic, engineering, political, defense, and legal sectors. Roads are one of the primary means of transportation that significantly impact the development and progress of a region by facilitating the movement of goods, services, and people. The purpose of this study is to determine the performance of the Maliana - Bobonaro road transportation section, which serves as a vital route connecting key areas and supporting local economic growth. This study utilizes the Calculation Capacity Road method based on the PKJI 2023 (Indonesian Road Capacity Guidelines) to assess road performance and travel time. The results of the study indicate that the Maliana – Bobonaro road section demonstrates good performance, with a capacity (C) of 2735.85 smp/hour, a degree of saturation of 0.235 and 0.195, and a level of service categorized as A and B. These results suggest that the road operates efficiently with minimal congestion, ensuring smooth traffic flow and reducing travel time. However, continuous monitoring and periodic evaluations are essential to maintain this performance level, especially with potential future increases in traffic volume due to regional development. This study provides valuable insights for policymakers and transportation planners in improving road infrastructure and ensuring sustainable transportation systems.